Trust chain generating and updating algorithm for dual redundancy system - Lei WANG; Ming-hua YANG; Zeng-liang LIU; Jian-qun ZHENG (Tongxin xuebao)
In trusted computing field,the traditional construction mode of trust chain is only applicable to a single system.For the dual redundancy system,it causes break of transitive trust.A trust model suitable for dual redundancy system was proposed.Through double trust chain design and IMC/IMV interaction mechanism,the trust chain extension of trust from a computing unit to another unit was realized.On this basis,a trust chain generating and update algorithm for dual redundancy system was proposed.Finally,the validity of the proposed model was proved based on the trusting theory.